Factors related to Muslim students' decision to enroll in Madrasah or other schools - Pandapatan, Abdulrahim-Tamano M. 1936-
Third and fourth year Muslim high school students from the madaris and other schools in Cotabato City, Marawi City, and Jolo, Sulu where the Maguindanaons, Maranaos, and Tausugs reside answered a questionnaire and were interviewed. The Maranao and Maguindanaon students do not differ in their choice of type of school but the Tausugs have a significantly greater preference for the madrasah than Maguindanaons or Maranaos. Male students have lower preference than females for the Madrasah. Fathers with low educational attainment prefer to educate their children in the madrasah, while fathers with high educational attainment, in other schools. Low income families prefer to enroll their children in the Madrasah.